Comparison of rhythm and rate control medications for new-onset atrial fibrillation in septic patients: MIMIC-IV database analysis - Cuilian Weng; Jian Lin; Qinghua Liu; Chang-hong Zou; Mingyu Zheng; Tingting Jiang; Linqian Jiang; Xiao-Feng Zhuang; Hangwei Feng (Journal of Translational Medicine)
Abstract Background The optimal management strategy for new-onset atrial fibrillation (NOAF) in patients with sepsis remains unclear. This study aimed to investigate and compare the associations of rhythm control medications versus rate control medications with mortality outcomes in septic patients with NOAF. Methods This propensity score-matched cohort study utilized data from the Medical Information Mart in Intensive Care-IV database. Adult septic patients with NOAF were categorized into two groups based on initial medications (rhythm or rate control). The primary outcome was 28-day mortality, with secondary outcomes including intensive care unit(ICU),1-year mortality. Results A total of 586 patients were included in the prematched cohort, with 277 patients remaining after propensity score matching. In the matched cohort, the primary outcome of 28-day mortality rate was 49.7% (85/171) in the rate control group and 46.2% (49/106) in the rhythm control group, with no significant difference between the groups (HR 0.97; 95% CI 0.68-1.37,P = 0.849). Secondary outcomes showed that rhythm control medications were not associated with increased ICU mortality (HR 1.03, 95% CI 0.60–1.78, P = 0.906) or 1-year mortality (HR 0.84, 95% CI 0.61–1.16, P = 0.299).However, the rhythm control group had higher successful cardioversion rates compared to the rate control group at 6 h (68.9% vs. 49.1%, P = 0.001), 12 h (71.1% vs. 52.4%, P = 0.002), and 24 h (72.7% vs. 53.2%, P = 0.002). Conclusions In septic patients with NOAF, rhythm control and rate control medications showed no difference in 28-day, ICU, or 1-year mortality.However, rhythm control may provide transient hemodynamic stabilization through rapid cardioversion, potentially beneficial during acute critical illness.